2012
DOI: 10.2486/indhealth.ms1253
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bronchoalveolar Lavage Fluid Adhering to Lung Surfactant

Abstract: Nickel oxide with two different particle sizes, micron size (NiO) and submicron size (nNiOm), as well as crystalline silica as a positive control and titanium dioxide as a negative control, were intratracheally instilled in rats and the phospholipid concentration and the protein concentration and surface tension of bronchoalveolar lavage fluid (BALF), which are used in surfactant assessment, were measured to see if they could be effective biomarkers in toxicity assessment. The results showed that the NiO insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…It showed the same threshold as in saline flooded lung, which indicates that intrapulmonary surfactant does not have an influence on HIFU cavitation in lung. This is conclusive to literature where it has been found that surface tension of BAL is almost identical to water [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…It showed the same threshold as in saline flooded lung, which indicates that intrapulmonary surfactant does not have an influence on HIFU cavitation in lung. This is conclusive to literature where it has been found that surface tension of BAL is almost identical to water [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In vitro studies have suggested that NiONPs induce pulmonary inflammation and genotoxic effects in lung cells 2‐5 . In our previous studies of intratracheal instillation of NiO particles administered to rats, samples of NiO particles with smaller diameters showed stronger inflammatory changes, 6,7 so we administered NiONPs to examine their inflammatory responses in rat lungs 8,9 . Inflammatory responses associated with NiONPs were stronger at three days after termination of a 4‐week inhalation exposure than at three days after an intratracheal instillation 10 .…”
Section: Introductionmentioning
confidence: 99%
“…76,100,101 Increased levels of SP-D, total protein, and phospholipids and decreased surface tension were detected in the BALF after NiO NP exposure. 44,[102][103][104] NiO NP exposure also caused a delayed-type hypersensitivity (DTH) response in rat lungs. 101 Environmental Science: Nano Critical review can recruit eosinophils in the lungs of rats by the direct release of intracellular eotaxin, but it was not related to the levels of total IgE and anaphylatoxins.…”
Section: Pulmonary Effects Of Nio Nps On Ratsmentioning
confidence: 99%